Application and Theory of Petri Nets and Concurrency 35th International Conference, PETRI NETS 2014, Tunis, Tunisia, June 23-27, 2014, Proceedings - Ciardo, Gianfranco; Kindler, Ekkart (Theoretical Computer Science and General Issues, 2014)
This book constitutes the proceedings of the 35th International Conference on Application and Theory of Petri Nets and Concurrency, PETRI NETS 2014, held in Tunis, Tunisia, in June 2014. The 15 regular papers and 4 tool papers presented in this volume were carefully reviewed and selected from 48 submissions. In addition the book contains 3 invited talks in full paper length. The papers cover various topics in the field of Petri nets and related models of concurrency.